2013
DOI: 10.1159/000355452
|View full text |Cite
|
Sign up to set email alerts
|

Familial Coaggregation of Alzheimer's Disease and Parkinson's Disease: Systematic Review and Meta-Analysis

Abstract: Background: Familial aggregation has been shown for Alzheimer's disease (AD) and Parkinson's disease (PD) separately, and it has been hypothesized that these diseases also coaggregate in families. Methods: The authors investigated familial coaggregation of AD and PD by conducting a systematic review and meta-analysis. PubMed was searched for relevant studies published through the end of October 2012. Three independent investigators screened publications and extracted data. Relative risk estimates of AD risk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“… 38 , 39 A recent systematic review that included 16 familial coaggregation studies of PD and Alzheimer’s disease concluded that there was only modest familial coaggregation of Alzheimer’s disease in individuals with PD-affected relatives (RRs: 1.18–1.40), which is consistent with our result. 40 Other psychiatric diseases, such as anxiety, depression, panic disorder, and phobia, are common non-motor presentations of PD, and their coaggregation with PD has been reported in previous studies, with RRs ranging from 1.45 to 1.87. 41 43 The modest familial coaggregation with PD implies that these psychiatric diseases might share common familial susceptibility factors with PD.…”
Section: Discussionmentioning
confidence: 80%
“… 38 , 39 A recent systematic review that included 16 familial coaggregation studies of PD and Alzheimer’s disease concluded that there was only modest familial coaggregation of Alzheimer’s disease in individuals with PD-affected relatives (RRs: 1.18–1.40), which is consistent with our result. 40 Other psychiatric diseases, such as anxiety, depression, panic disorder, and phobia, are common non-motor presentations of PD, and their coaggregation with PD has been reported in previous studies, with RRs ranging from 1.45 to 1.87. 41 43 The modest familial coaggregation with PD implies that these psychiatric diseases might share common familial susceptibility factors with PD.…”
Section: Discussionmentioning
confidence: 80%
“…Since key pre-existing medical conditions and behavioral factors (e.g., smoking, physical activity) were accounted for in our study, this suggests that changes in other factors over time may have contributed to the increased incidence trends in longer-term immigrants. Other potential drivers to consider in future research includes environmental exposures (e.g., air pollution and toxins), health care access, stress, adjustments to new environments, and gene-environment exposures 24,[57][58][59] . Protective effects may also have been present in the countries of origin.…”
Section: Comparison Of Results With Previous Literaturementioning
confidence: 99%
“…That pathological mechanism could accelerate the accumulation of amyloid and toxic substances in brain, resulting in increased risk of AD [32]. In addition, Individuals who have a parent, brother or sister with AD are more likely to develop the disease than those who do not have a first-degree relative with AD [33, 34], which could be explained by the genetic factors more or less.…”
Section: Discussionmentioning
confidence: 99%